Financial Management for Higher Education Affirmation Students (ADIK) from Papua in West Sumatra - Ria Anggraini Tuarita; Nailal Husna; Ice Kamela; Zeshasina Rosha; Irda Irda (ProBisnis : Jurnal Manajemen, 2026)
This research aims to analyse the impact of financial literacy, pocket money, and self-control on personal financial management among students of the Higher Education Affirmation Programme (ADIK) from Papua in West Sumatra. The sample size utilised in this study comprises 94 respondents, with the sampling method employing a census approach, whereby the entire population is considered as the sample. The data analysis technique employed is multiple linear regression analysis, alongside the T-test, with data processed using Stata 17. The type of data in this study is quantitative, and the data source is primary data. Based on the results of hypothesis testing, it was found that financial literacy and pocket money have a positive effect on personal financial management, where financial knowledge and economic resources improve financial management skills. Meanwhile, self-control has no positive effect on personal financial management among students of the Higher Education Affirmative Program from Papua in West Sumatra. The results of this study encourage universities in West Sumatra, as well as the Papuan regional government and the Ministry to integrate programs such as digital-based workshops to maximize pocket money, allocate pocket funds to reduce the risk of waste, and discussions among Papuan students to share financial experiences.